Aleut dwelling (Barabara) at Unalaska, Alaska, July 1899. - Curtis, Edward S., 1868-1952
From album entitled: A Souvenir of the Harriman Alaska Expedition, May - August, 1899. Volume II, Cook Inlet to Bering Strait and the Return Voyage, leaf 149. Caption on image: Barabara--Iliuliuk Photograph taken by Edward S. Curtis, official photographer, member of the 1899 Harriman Alaska Expedition.